The mediating role of crew health in service quality - Joanna Gabriella; Edhie Budi Setiawan; Theresye Yoanyta Octora; Amrulloh Ibnu Kholdun; Lira Agusinta (Annals of Human Resource Management Research, 2025)
Purpose: This study examines the relationship between ship chandler service quality (specifically responsiveness, reliability, and product quality) and crew satisfaction, with crew health as a mediating variable. The research highlights the critical role of ship chandler services in supporting crew well-being, especially when access to essential supplies was restricted. Research Methodology: This quantitative study surveyed 150 crew members from 52 PIS-owned vessels using PMSol services, selected through purposive sampling, and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings reveal that crew satisfaction is significantly influenced by responsiveness, reliability, and product quality. Moreover, crew health acts as a mediating variable, strengthening the impact of service and product quality on satisfaction. High-quality, reliable, and responsive services (both directly and indirectly) enhance crew happiness and well-being. Conclusions: Ship chandler services that are responsive, reliable, and provide high-quality products not only meet logistical needs but also enhance crew well-being and satisfaction. Recognizing crew health as a key factor can help maritime service providers design more human-centered support systems, especially during challenging times like a pandemic. Limitations: The study focuses solely on crew members aboard PIS-owned vessels using PMSol services, which may limit the generalizability of the findings to other companies or contexts. Contribution: Study highlights crew health as key mediator, linking service quality to satisfaction in maritime services.